Motives for the Influx of Moroccan Scholars and Traders to West Africa and Their Settlement in the Region During the Modern Period - Aouatef, DOUDI (Journal of Ecohumanism, 2026)
This research paper aims to highlight the primary motives behind the movement of Moroccan scholars and merchants towards West Africa during the modern period, specifically from the 16th to the 19th centuries. This research includes a set of important elements through which it attempts to trace and analyze the motivations behind this influx, which played a pivotal role in building bridges of cultural exchange and strengthening commercial and cultural ties between the two regions. Discussing this topic presents numerous challenges due to several factors, as this presence was not a recent phenomenon—a product of this period alone—but rather dates back to a very ancient era, to the point that some attribute it to the period before the advent of Islam in the Maghreb. However, it undoubtedly intensified with the arrival of Islam. Therefore, it remains difficult to distinguish between the factors contributing to their migration and its increase during the period under study.